Study guides

Q: How do you graph -3x plus y equals -6?

Write your answer...

Submit

Related questions

Rearrange the equation to read : y = 6 - 3x and graph normally.

The starting point on the y-axis changes from -2 to 6.

2x + 3x + 6 = 5x + 6

3x + 2 = 3x + 6 This is not possible.

what is a slope

3x+y=6

First of all, if 'x' is 3, then 'x' doesn't equal -3x+3 . You must mean y = -3x + 3.If x=3, then (-3x + 3) = -6 .The graph is the point (3, -6) .

x=6

-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2

It is a singular matrix.

X equals 9.

-2

x=5

x=-5

x = 5

x = 2

51

5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5

y = 3x + 6slope = 3

y=3x+b where b≠6 is any real number.

y = 3x =3(6) = 18 ... the ordered pair is (x,y) = (6,18)

-2

-3x+9y = 6 9y = 3x+6 y = 1/3x+2/3

x = -4 and y = 2

If 3x + 3 = 2x + 6 then 3x - 2x = 6 - 3 x = 3